The Impact of Multimodal Vocabulary Instruction On The Acquisition And Retention of English Vocabulary Among Young EFL Learners In Rural Settings - Helmi (EduCurio: Education Curiosity, 2023)
This study investigates the effectiveness of multimodal vocabulary instruction in enhancing the acquisition and retention of English vocabulary among young English as a Foreign Language (EFL) learners in rural educational settings. Utilizing a quasi-experimental design, the research involved a sample of [insert number] participants from [insert location], who were divided into experimental and control groups. The experimental group received instruction incorporating a variety of sensory modalities, including visual aids, audio resources, and interactive activities, while the control group received traditional vocabulary instruction methods. Pre- and post-assessment measures, including vocabulary tests and retention assessments, were administered to both groups. The results demonstrated a statistically significant improvement in vocabulary acquisition and retention among the participants who received multimodal instruction. Additionally, qualitative data gathered through interviews and observations provided insights into the learners' engagement and preferences for multimodal approaches. This research contributes to the growing body of literature on effective pedagogical strategies for EFL learners, particularly in under-resourced rural contexts, emphasizing the value of multimodal instruction in enhancing vocabulary learning outcomes. Implications for classroom practices and recommendations for further research are discussed.